2006
DOI: 10.1016/j.dsr2.2005.10.019
|View full text |Cite
|
Sign up to set email alerts
|

How entraining density currents influence the stratification in a one-dimensional ocean basin

Abstract: The sensitivity of the basin-scale ocean stratification to the vertical distribution of plume entrainment is being analyzed. A large ocean basin supplied by dense water from an adjoining marginal sea is considered. The dense water flows into the ocean basin as an entraining density current and interleaves at the bottom (or at the level of neutral density), where it deposits a mixture of marginal seaand basin water. As the basin water, i.e. 'old' plume water, is entrained and re-circulated in the plume a strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
(86 reference statements)
2
22
0
Order By: Relevance
“…Furthermore, for low F r and low Re, it had a comparable order of magnitude to mixing observed in the ocean. As already pointed out by Wåhlin & Cenedese (2006) and Hughes & Griffiths (2006), the subcritical mixing observed in CWAO and in some of the present experiments, could be of fundamental importance when determining the final water mass characteristics (for example density) of a dense current descending the continental slope following a long path. Therefore, a weak, but non-zero, entrainment can substantially change the final density and, consequently, the location of important water masses, such as NADW, in the open ocean water column.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, for low F r and low Re, it had a comparable order of magnitude to mixing observed in the ocean. As already pointed out by Wåhlin & Cenedese (2006) and Hughes & Griffiths (2006), the subcritical mixing observed in CWAO and in some of the present experiments, could be of fundamental importance when determining the final water mass characteristics (for example density) of a dense current descending the continental slope following a long path. Therefore, a weak, but non-zero, entrainment can substantially change the final density and, consequently, the location of important water masses, such as NADW, in the open ocean water column.…”
Section: Discussionmentioning
confidence: 68%
“…This new parameterization will, consequently, differ substantially from the Ellison & Turner (1959) parameterization still widely used. The Wåhlin & Cenedese (2006) comparison of the Ellison & Turner (1959) and CWAO low-Froudenumber parameterization suggests that major differences in the basin stratification could occur, in the case of small slopes, depending on the parameterization used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it assumes that the amount of entrainment in a dense current descending down a slope depends on both the Froude number Fr and Reynolds number Re of the flow and that entrainment occurs for subcritical Fr (,1). The subcritical entrainment observed in Cenedese et al (2004) and Cenedese and Adduce (2008) has been suggested (Wå hlin and Cenedese 2006;Hughes and Griffiths 2006;Lauderdale et al 2008) to be of fundamental importance for the water mass characteristics, such as density, of a dense current descending the continental slope. A weak, but nonzero, entrainment can change the final density and, consequently, the depth and location of important water masses in the open ocean.…”
Section: A New Parameterizationmentioning
confidence: 99%
“…4 Now as the new overflow entrainment parameterizations are implemented into coupled climate models, we are beginning to investigate the influence of overflow entrainment on the large-scale circulation and, therefore, climate. We are guided by work carried out in idealized ocean models, which suggest that overflow entrainment can significantly influence the MOC and large-scale ocean stratification (Hughes and Griffiths 2006;Wahlin and Cenedese 2006). Early results from the NCAR and GFDL OGCMs 4 These earlier studies did not include physically based parameterizations of the entrainment in overflows but rather focused on limiting the excessive spurious entrainment in the z-coordinate models.…”
mentioning
confidence: 99%